A male with ill-fitting skin with dyspnea - Zade, Tushar Pawan; Pandharipande, Madhuri S; Joshi, Rakhee W; Nagpure, Yugal (Indian Journal of Case Reports, 2025)
Scleroderma/systemic sclerosis (SSc) is an orphan disease of unknown etiology, complex pathogenesis, and variable clinical presentations. SSc frequently follows a progressive course and is associated with significant disability and mortality. SSc shows a strong female predominance (4.6:1) as compared to males. The onset of skin manifestation to its progression to systemic features is early among males as compared to their female counterparts. Also, they have rapid clinical and biochemical deterioration. In this case report, we present the case of a 33-year-old male scleroderma with early lung involvement without renal manifestation and deliberate regarding variation of clinical manifestation in male patients in comparison to female counterparts.